Diamond Nanoparticles Downregulate Expression of CycD and CycE in Glioma Cells - Marta Grodzik (Molecules, 2019)
Our previous studies have shown that diamond nanoparticles (NDs) exhibited antiangiogenic and proapoptotic properties in vitro in glioblastoma multiforme (GBM) cells and in tumors in vivo. Moreover, NDs inhibited adhesion, leading to the suppression of migration and invasion of GBM. In the present study, we hypothesized that the NDs might also inhibit proliferation and cell cycle in glioma cells. Experiments were performed in vitro with the U87 and U118 lines of GBM cells, and for comparison, the Hs5 line of stromal cells (normal cells) after 24 h and 72 h of treatment. The analyses included cell morphology, cell death, viability, and cell cycle analysis, double timing assay, and gene expression (Rb, E2F1, CycA, CycB, CycD, CycE, PTEN, Ki-67). After 72 h of ND treatment, the expression level of Rb, CycD, and CycE in the U118 cells, and E2F1, CycD, and CycE in the U87 cells were significantly lower in comparison to those in the control group. We observed that decreased expression of cyclins inhibited the G1/S phase transition, arresting the cell cycle in the G0/G1 phase in glioma cells. The NDs did not affect the cell cycle as well as PTEN and Ki-67 expression in normal cells (Hs5), although it can be assumed that the NDs reduced proliferation and altered the cell cycle in fast dividing cells.